Household Food Security Status And Food Feeding Culture With Stunting Incidence: A Cross-Sectional Study Among Children 24- 59 Months In Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
Introduction: Low levels of food consumption for a long time due to food insecurity and inappropriate food feeding culture can lead to chronic nutritional deficiencies, which can manifest as stunting. This study aims to determine the relationship between household food security status, food feeding culture, and the incidence of stunting in toddlers aged 12–59 months. Methods: The research involved the design of a cross-sectional analysis. The sample in this study was 103 toddlers registered at the Integrated Healthcare Centre in the working area of Pujer Public Health Centre, Bondowoso Regency, East Java, Indonesia. Sampling technique: proportional random sampling. The instruments used are the microtoice, the US-HFSSM questionnaire and the Child Feeding Questionnaire (CFQ). Data analysis using the Chi-square test. Result: The results showed that most toddlers are female (54.4%) and have normal nutritional status (64.1%). Toddlers have a household status of food security (58.3%) and an appropriate Food Feeding Culture (64.1%). While the results of the chi-square test show that there is a significant relationship between household food security status (p-value=0.000) (OR= 0.219), there is also a significant relationship between food feeding culture (p-value=0.004) (OR=0.295). Conclusion: The household food security status and food feeding culture is related to the incidence of stunting in toddlers. For this reason, efforts to strengthen food self-sufficiency at the household level are expected. Such as intensification of yards through the Sustainable Food Home Area programme and local food diversification.